G263 MRCPCH Clinical Success Initiative (CSI). (7th April 2014) - Ferguson, EC; Bryan, JN; Ellis, JA; McMahon, A
Abstract : Background: The Membership of the Royal College of Paediatrics and Child Health (MRCPCH) clinical examination, represents the final hurdle for paediatric trainees in achieving full membership of the college and is necessary for training progression. In our locality, the MRCPCH clinical examination pass rate had raised concerns. Repeated examination attempts are stressful, financially demanding, and can affect career progression. Examination failure can impact significantly on workforce planning. Aim: To introduce a revision initiative for paediatric trainees to improve the MRCPCH clinical pass rate. Method: Locally, prior to October 2012, revision sessions were organised by trainees themselves, with more senior trainees and consultants supporting candidates with ad-hoc teaching sessions prior to the examination. Commencing prior to the 3rd 2012 clinical examination sitting, the local Postgraduate Medical Education (PGME) department initiated a structured revision timetable for trainees in the six weeks prior to the clinical examinations. Results: MRCPCH Clinical examination pass rates were reviewed prior to, and after the introduction of the programme. Comparisons have been drawn within the deanery and nationally. Trainees have given anonymised feedback on the programme. All trainees undertaking the MRCPCH Clinical examination since the initiative was launched have engaged with the programme and trainee feedback has been unanimously positive. Table 1 illustrates the improvement in the local examination pass rate following the introduction of the CSI, from 43.3% in the preceding year to 78.5%. The local pass rate is now surpassing both the deanery-wide and the national pass rates (see Graph 1). Discussion: PGME organisation has facilitated targeted training, improved teaching attendance, and allowed consultant flexibility to organise opportunistic teaching in a co-ordinated manner with selected cases. Significantly, since the introduction of this initiative, no outcome 4 has been given to any trainee. Conclusion: The success of this initiative highlights the benefits for trainees of a supportive revision programme at local level in improving examination success.